Self-Understanding Intelligence to Improve Student Achievement in Islamic Boarding Schools in Thailand - Mr. Anat Maisu; Abdulrohim E-sor (Walidem Institute and Publishing (WIP), 2024)
This study aims to analyze the influence of self-understanding intelligence in improving student achievement in Islamic boarding schools in Thailand. Self-understanding intelligence, which includes self-understanding, emotional control, and motivation management, is believed to play an important role in the learning process of students. The research method used is a quantitative approach with a survey design, involving students in several Islamic boarding schools in Thailand as respondents. Data collection was carried out through questionnaires measured by the Likert scale, as well as in-depth interviews to support the quantitative findings. The results of the study show that self-understanding intelligence contributes significantly to the improvement of student's academic achievement. Students who have good self-awareness and can manage their emotions show better performance in the classroom. The novelty of this study is the emphasis on the role of self-understanding intelligence in the context of pesantren education, which has not been widely researched, especially in Thailand. The implications of this study show the importance of developing programs that support students' self-understanding intelligence in the pesantren curriculum. This is expected to increase the effectiveness of learning and academic achievement, as well as help students in facing emotional and social challenges in the pesantren environment.